Caught in the Crossfire: How Work-Family Conflict Affects the Lives of Married Nurses in India - Khateeb, Fatima Riyaz (SEISENSE Journal of Management, 2023)
Purpose- This research aimed to examine the nature of the relationship between work and life among married nurses in Jammu and Kashmir, IndiaDesign/Methodology- A questionnaire with measures for work-family conflict, life satisfaction, and family satisfaction was administered. The nodal agency, Government Medical College (GMC), provided the researcher with a list of nurses and their marital statuses. A sample of 253 nurses was analyzed using simple random sampling from a list of potential 527 nurses. These 253 respondents worked at five major government hospitals. In addition to the work-family measures, questions on age, work experience, job grade, and family type were askedFindings- The results revealed a significant relationship between work and family conflict with both life satisfaction as well as family satisfaction. In both cases, the time-based, and strain-based conflict scored higher than the behavior-based conflict in influencing family and life satisfaction negativelyPractical Implications- The results highlight the need for organizational support for nurses, which can be in the form of flexible work schedules, and other time-saving techniques. Given that nurturing responsibilities are shouldered by women in India not only monetary but non-monetary benefits should be availed to the nurses to alleviate their work-family conflict.